The PI3K/AKT pathway promotes gefitinib resistance in mutant KRAS lung adenocarcinoma by a deacetylase‐dependent mechanism. Issue 11 (13th December 2013) - Jeannot, Victor; Busser, Benoît; Brambilla, Elisabeth; Wislez, Marie; Robin, Blaise; Cadranel, Jacques; Coll, Jean‐Luc; Hurbin, Amandine
<x xml:space="preserve">Abstract</x> To select the appropriate patients for treatment with epidermal growth factor receptor tyrosine kinase inhibitors (EGFR‐TKIs), it is important to gain a better understanding of the intracellular pathways leading to EGFR‐TKI resistance, which is a common problem in patients with lung cancer. We recently reported that mutant KRAS adenocarcinoma is resistant to gefitinib as a result of amphiregulin and insulin‐like growth factor‐1 receptor overexpression. This resistance leads to inhibition of Ku70 acetylation, thus enhancing the BAX/Ku70 interaction and preventing apoptosis. Here, we determined the intracellular pathways involved in gefitinib resistance in lung cancers and explored the impact of their inhibition. We analyzed the activation of the phosphatidyl inositol‐3‐kinase (PI3K)/AKT pathway and the mitogen‐activated protein kinase/extracellular‐signal regulated kinase (MAPK/ERK) pathway in lung tumors. The activation of AKT was associated with disease progression in tumors with wild‐type EGFR from patients treated with gefitinib (phase II clinical trial IFCT0401). The administration of IGF1R‐TKI or amphiregulin‐directed shRNA decreased AKT signaling and restored gefitinib sensitivity in mutant KRAS cells. The combination of PI3K/AKT inhibition with gefitinib restored apoptosis via Ku70 downregulation and BAX release from Ku70. Deacetylase inhibitors, which decreased the BAX/Ku70 interaction, inhibited AKT signaling and induced gefitinib‐dependent apoptosis. The PI3K/AKT pathway is thus a major pathway contributing to gefitinib resistance in lung tumors with KRAS mutation, through the regulation of the BAX/Ku70 interaction. This finding suggests that combined treatments could improve the outcomes for this subset of lung cancer patients, who have a poor prognosis.